(3dZI GdbQBf aj HjGf SHd GdTjWGf (B/s - (3MSf, YGOd eMeO EHQGgjes ((3GdbGgQI (B:s (3OGQ GdBaGb GdYQHjI ,s, 2016)
(3MJi jfLM GdTjWGf aj COGA egeJg hJJMbb ZGjJg aj EVdGd Hfj GdHTQ hGJHGYge dghGg de jcf djSdc eSdcG hGMOG dG jMjO Yfg MJi jMPQhg hjYQVhG Yfg, hdcf JTcdJ UhQg hGNJdaJ MJi EPG aTd aj JMbjb egeJg aj UhQI eG dLC Edi CNQi MJi jUd Edi eG jUHh Edjg, hgPg GdUhQ GdeJZGjQI hGdCTcGd GdeNJdaI bO jJLg HgG Edi Hfj BOe LejYG Ch Edi WGFaI efge, hef gfG XgQJ SHdg GdYGeI hGdNGUI ceMWI ef eMWGJ GdJeMjU hGdGHJdGA hGdGNJHGQ eOQcG LejY NUGd GdHTQjI hfhGRYgG GdeNJdaI hGJLGgGJgG GdeJYOOI eJbfG CHLOjGJ dZJge aJCJj JUQjMGJg hJdejMGJg HeG jJdGAe hjJhGab eYgG hPdc aj EHOGY YLjH hfXe HOjY JbOeg CdaGX GdbQBf GdcQje(B.s
(3HHdjhLQGajI (B: (3UaMI (B115-118.s
Keywords: (3GdTjGWjf hGdLGf aj GdbQBfs; (3GdbQBfs -- (3eHGMK YGeI s